2018
DOI: 10.31223/osf.io/kh6j9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landers 1992 "reloaded": Integrative dynamic earthquake rupture modeling

Abstract: Key Points:• A new integrative physics-based simulation of the 1992 Landers earthquake reproduces a broad range of independent observation • Sustained dynamic rupture interconnecting the complex fault segments constraints pre-stress and fault strength • We discuss the interplay of rupture transfers, geometric fault complexity, initial stress, viscoelastic attenuation, and off-fault plasticity AbstractThe 1992 M w 7.3 Landers earthquake is perhaps one of the best studied seismic events. However, many aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 101 publications
(233 reference statements)
3
34
0
Order By: Relevance
“…Significant inelastic off‐fault deformation has recently been documented for continental earthquakes (e.g., Dolan & Haravitch, ; Milliner et al, ; Rockwell et al, ; Zinke et al, , ). Dynamic rupture models (e.g., Kaneko & Fialko, ; Roten et al, ; Wollherr et al, ) showed that inelastic off‐fault deformation reduces fault slip at shallow depths, consistent with our subduction zone model results, which can explain the shallow slip deficit of earthquakes inferred from geodetic data (e.g., Fialko et al, ). We suggest that if shallow slip deficit is significant on continents, it is likely more significant in shallow subduction zones, due to low strength of marine sediments and possible high pore fluid pressure (e.g., Saffer & Tobin, ) in enhancing inelastic deformation.…”
Section: Discussionsupporting
confidence: 87%
“…Significant inelastic off‐fault deformation has recently been documented for continental earthquakes (e.g., Dolan & Haravitch, ; Milliner et al, ; Rockwell et al, ; Zinke et al, , ). Dynamic rupture models (e.g., Kaneko & Fialko, ; Roten et al, ; Wollherr et al, ) showed that inelastic off‐fault deformation reduces fault slip at shallow depths, consistent with our subduction zone model results, which can explain the shallow slip deficit of earthquakes inferred from geodetic data (e.g., Fialko et al, ). We suggest that if shallow slip deficit is significant on continents, it is likely more significant in shallow subduction zones, due to low strength of marine sediments and possible high pore fluid pressure (e.g., Saffer & Tobin, ) in enhancing inelastic deformation.…”
Section: Discussionsupporting
confidence: 87%
“…Such models provide physically self‐consistent earthquake source descriptions by modeling spontaneous frictional failure across a predefined fault coupled to seismic wave propagation. By using modern numerical methods and hardware specific software optimization, dynamic rupture simulations can reach high spatial and temporal resolution of increasingly complex geometrical and physical modeling components (Wollherr, Gabriel, & Mai, ; Ulrich, Gabriel, et al, ). In comparison to the aforementioned approaches, such models fully incorporate inertia effects as well as the nonlinear interaction of seismic waves and fault mechanics governed by friction.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to highlight that both of these methods omit manual mesh-generation, which is typically required as a pre-processing step in computational seismology applications and poses a major bottleneck. Hexahedral mesh generation can easily consume weeks to months and is limited for complex geometries of boundary and interface conditions, while form-fitted unstructured tetrahedral meshes allow for automatised meshing and complex geometries [56,57], however, pose numerical challenges, e.g. in form of misshaped sliver elements [58].…”
Section: Elastic Wave Equationmentioning
confidence: 99%